Matemática
wesley0007
7

Sejam as funções f(x) = x²-2x+1 e g(x) = 2x+1, calcule: a) (fog)(x) b) (gof)(2)

+0
(1) Respostas
myrna

Lembre: [latex]fog(x)=f(g(x))\\gof(x)=g(f(x))[/latex] ______________________ a) fog(x) [latex]fog(x)=f(g(x))[/latex] [latex]f(x)=x^{2}-2x+1\\f(g(x))=[g(x)]^{2}-2[g(x)]+1\\fog(x)=[2x+1]^{2}-2[2x+1]+1\\fog(x)=[(2x)^{2}+2*2x*1+1^{2}]-4x-2+1\\fog(x)=[4x^{2}+4x+1]-4x-1\\fog(x)=4x^{2}+4x-4x+1-1\\fog(x)=4x^{2}[/latex] b) [latex]gof(2)=g(f(2))[/latex] [latex]f(x)=x^{2}-2x+1\\f(2)=2^{2}-2*2+1\\f(2)=4-4+1\\f(2)=1[/latex] [latex]g(f(2))=g(1)\\g(x)=2x+1\\g(1)=2*1+1\\g(1)=2+1\\g(1)=3[/latex] [latex]\boxed{\boxed{gof(2)=3}}[/latex]

Adicionar resposta